2018
DOI: 10.1177/0954410018804737
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady aerodynamics investigation of deploying tandem-wing with different methods

Abstract: In the rapidly deploying process of the unmanned aerial vehicle with folding wings, the aerodynamic characteristics could be largely different owing to the effects of deformation rate and the aerodynamic interference. The investigation on the unsteady aerodynamics is of great significance for the stability analysis and control design. The lifting-line method and the vortex-lattice method are improved to calculate the unsteady aerodynamics in the morphing stage. It is validated that the vortex-lattice method pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Cheng et al investigated the unsteady aerodynamics in the morphing stage of a tandem-wing UAV by using the improved vortex lattice method. This research confirmed that the vortex-lattice method can accurately predict the unsteady aerodynamic performance [12]. Besides, the same team also proposed a method of predicting the lift coefficient of tandem-wing aircraft systems based on Prandtl's lifting-line theory [13].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Cheng et al investigated the unsteady aerodynamics in the morphing stage of a tandem-wing UAV by using the improved vortex lattice method. This research confirmed that the vortex-lattice method can accurately predict the unsteady aerodynamic performance [12]. Besides, the same team also proposed a method of predicting the lift coefficient of tandem-wing aircraft systems based on Prandtl's lifting-line theory [13].…”
Section: Introductionsupporting
confidence: 59%
“…Xie data from the wind tunnel tests [37]. Our previous comparative work, which used CFD method, adequately validated the accuracy and capability of non-linear VLM when calculating aerodynamic characteristics for tandem-wing aircraft [11], [12]. The results are shown in Fig.…”
Section: ) Validation Of the Numerical Calculation Methodsmentioning
confidence: 58%
“…Compared with results obtained by different methods proposed in the previous study, the VLM method is more accurate to calculate the unsteady aerodynamics during the deploying process. 48 In order to apply the boundary condition that the flow in the direction normal to the wing's surface is zero, on all the lifting surfaces, the wing's mean camber surfaces should be divided into trapezoidal elements on which the discrete vortex rings are placed. The leading-edge segment of each vortex ring coincides with the quarter chord line of the corresponding element, and the control point is set at the midpoint of the three-quarter chord line of the element.…”
Section: Aerodynamics Calculationmentioning
confidence: 99%
“…Besides, in our previous study, the VLM and the lifting-line method were proposed to calculate the unsteady aerodynamics of the tandem wing aircraft during its deploying process, and meanwhile, the effects of the layout parameters and the deformation rate were studied comprehensively. 48 After launching from the tube, the lifting surfaces deploy by rotating around a hinge axis perpendicular to the airframe axis. During the deploying process, swept angles of the fore and hind wing change until fully deployed.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4(c) shows the mesh generated for the present study, and most region is filled with structured mesh for good converging speed. 33 The meshes are refined in the region where shock waves and fierce evaporation occur to capture the discontinuity through shocks and mass transfer, which is marked by red oval. Note that the ozx plane and the oyz plane are the most representative profiles inside a silo.…”
Section: Computational Modelmentioning
confidence: 99%